2013
DOI: 10.1111/hae.12335
|View full text |Cite
|
Sign up to set email alerts
|

An approach to outreach patients with von Willebrand disease in Egypt by targeting women with heavy menstrual bleeding and/or bleeding symptoms

Abstract: von Willebrand disease (VWD) is frequently ignored as a cause of menorrhagia. We investigated Egyptian women complaining of heavy menstrual bleeding (HMB) and/or other bleeding symptoms to detect potential VWD cases. Seventy-five female patients complaining of HMB and/or bleeding symptoms and 38 age-matched healthy female controls went through a family history questionnaire, a physical examination and were evaluated for bleeding score, pictorial blood assessment chart (PBAC), complete blood count, serum ferrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…The present study revealed that a family history of bleeding disorders was signi cantly more common among menorrhagic women than among non-menorrhagic women; however, approximately 3-fold more menorrhagic women did not have any family history of bleeding disorders. These ndings are consistent with studies performed in Egypt (29), Sudan (25) and Sweden (30). Previous studies have shown a substantial association between idiopathic menorrhagia and a family history of heavy menstrual bleeding, suggesting that familial menorrhagia is an inherited feature (27).…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that a family history of bleeding disorders was signi cantly more common among menorrhagic women than among non-menorrhagic women; however, approximately 3-fold more menorrhagic women did not have any family history of bleeding disorders. These ndings are consistent with studies performed in Egypt (29), Sudan (25) and Sweden (30). Previous studies have shown a substantial association between idiopathic menorrhagia and a family history of heavy menstrual bleeding, suggesting that familial menorrhagia is an inherited feature (27).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, in healthcare systems where nurses can pursue recognition as advanced practice providers (APP), there is evidence that the APP can expand outreach and services to patients with bleeding disorders 37 . One approach in Egypt demonstrated that screening with questionnaires can help identify appropriate candidates for referral to an HTC for further evaluation and laboratory testing 38 …”
Section: Resultsmentioning
confidence: 99%
“…In women with VWD, menorrhagia is the most common symptom. [7,8] It is also substantially unknown whether different bleeding symptoms may preferentially cluster together with some particular pattern within VWD patients, and whether the presence of some bleeding symptoms may actually predict occurrence of bleeding in circumstantial situations (e.g. surgery).…”
Section: Introductionmentioning
confidence: 99%